Madurese Typology and Characteristics Amelioration in Ahmad Sapardi's Short Story Pelean Klebun: Semiotics Analysis (NOBEL: Journal of Literature and Language Teaching, 2018)
This article aims to identify Madurese typology and characteristics within the short story Pelean Klebun by focusing on lexicon â€œKerasâ€ and â€œPedasâ€ to produce new meaning and perspective of Madurese typology and characteristics. This article uses model of Semiotics analysis by Charles Sanders Peirce as methodological process to identify and create a new meaning and perspective on Madurese. The result of the analysis is Madurese typology and characteristics are depicted in lexicon â€œKerasâ€ and â€œPedasâ€, and supposed to produce two perspectives within the short story. As conclusion, â€œKerasâ€ and â€œPedasâ€ undergo a process of amelioration textually within the short story and contextually within various researches about Madurese local wisdom that reflects Madurese typology and characteristics.